Tan Malaka : Pendidikan sebagai Langkah Pertama Manusia Indonesia Merdeka 100% - Wahyu Trisno Aji; Marzuki Marzuki; Nanang Zakaria (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This study aims to explain Tan Malaka's ideas about education as the first solution to freeing the Indonesian nation from colonialism and to realize 100% Indonesian independence. This study uses a qualitative-descriptive type with a library research approach, using documentation data collection techniques, so that researchers do not need to go to the field to get information, but collect data from literature sources related to the topic being studied, using data analysis techniques in the form of data reduction, data presentation, and conclusions. The results of this study are that Indonesia with all the turmoil of problems in the 21st century began to be questioned, is it true that Indonesia is independent and all Indonesian people feel the independence. This question was once raised by the Father of the Republic of Indonesia with a burning spirit to rebuild Indonesia as 100% independent. Education for Tan Malaka is the first step for the Indonesian nation to build quality human resources, then the impact of education is that it can successfully escape from colonialism in any form, Tan Malaka initiated a type of education where all parties can access which is called education for the Indonesian people. He also explained three sources of education, including religion, humans and nature.